Effects of frequency on fade slope based on measured rain attenuation data in Malaysia - Islam, Md. Rafiqul; Chebil, Jalel; Dao, Hassan; M., Al-Hareth (2010)
There is an ever increasing demand for radio-frequency (RF) spectrum by the nations of the world, in order to satisfy the growing demand for long-distance communications. As C-band (4/6 GHz) is already congested, and Ku-band (12/14 GHz) is filling up rapidly, currently interest focus on the utilization of higher bands. Some systems are already designed to operate at Ka-band (20/30 GHz), and it is probable that serious consideration to utilize V-band (40/50 GHz) in the future will be given. However, when operating at the higher frequency Ku-band, the strength of the signal may be temporarily reduced under severe rain conditions. Rain attenuation is an obstacle in a design of radio systems especially in microwave frequencies. Generally, rain attenuation increases as the signal frequency increases, but does this affect the fade slope which is defined as the rate of change of attenuation in (dB/s). This paper will highlight the effect of frequency on fade slope based on measured data of rain attenuation in Malaysia between May 1998 to April 2000 at four different frequencies (15, 23, 26 and 38GHz). The effect of the link length will be also highlighted.